(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The study was conducted to determine the effect of Leucaena at different proportions and doses of molasses on the nutritional quality, silage fermentation characteristic, and in vitro digestibility of corn stover silage. Materials and Methods: The study was designed in a completely randomized factorial design 3*3 pattern. The first factor was the proportion addition of Leucaena, i.e., L0 (0%), L15 (15%), L30 (30%), and L45 (45%) of inclusion of Leucaena on the dry matter (DM) basis of corn stover. The second factor was the dose of inclusion of molasses, i.e., M2 (2%), M4 (4%), and M6 (6%) on the fed basis of silage. Each treatment had five replications. The variables observed included chemical composition [DM, organic matter (OM), crude protein (CP), crude fiber (CF), hemicellulose, acid detergent fiber, and neutral detergent fiber], silage fermentation characteristics (pH and NH3 -N), DM digestibility (DMD), and OM digestibility (OMD) under in vitro conditions. Results: The result shows that the inclusion of Leucaena in the proportion of 30%–45% is very effective in increasing and improving the chemical composition of corn stover silage, significantly suppresses the content of CF, and increases the CP content of the silage. Likewise, the inclusion of molasses at a dose of 4% also positively contributed to the quality of the resulting silage, especially its effect in suppressing the buffer capacity of proteins resulting in low pH values and NH3 -N concentrations in silage. Conclusions: It was concluded that the inclusion of Leucaena in 30%–45% and the inclusion of molasses at a dose of 4% is very effective in increasing and improving the chemical composition, silage fermentability characteristics, and rumen degradation of corn stover silage. J. Adv. Vet. Anim. Res., 10(1): 118–125, March 2023 http://doi.org/10.5455/javar.2023.j660